1976
DOI: 10.3758/bf03204243
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous time and size perception

Abstract: Judgments of the apparent duration and size of visually presented circles vary directly with the duration and size of the presented stimuli. When the frequencies of stimulus duration (short vs. long) and stimulus area (small vs. large) are varied, perceived size and duration are directly related to the frequency of the lower attribute value (short or small). These data are compared to the predictions of different information-processing models. The model which accounts for the data best is one in which it is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
24
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 11 publications
5
24
0
Order By: Relevance
“…We offer two tentative explanations for this finding. The first is based on the finding that time seems longer as the number of units of information processed per unit of time is increased (Thomas & Cantor, 1976). As the clock-monitors had to process more information as a function of the clockmonitoring task and as they also worried more about how long it was taking them to fall asleep, this group is likely to have processed more information units, which may have constituted a psychological basis for time overestimation.…”
Section: Discussionmentioning
confidence: 99%
“…We offer two tentative explanations for this finding. The first is based on the finding that time seems longer as the number of units of information processed per unit of time is increased (Thomas & Cantor, 1976). As the clock-monitors had to process more information as a function of the clockmonitoring task and as they also worried more about how long it was taking them to fall asleep, this group is likely to have processed more information units, which may have constituted a psychological basis for time overestimation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that perception of temporal duration depends upon various factors. That is, perceived duration increased with frequency of attending to the lapse of time (Fraisse, 1984), perceived numbers of events during that period (Brown, 1995;Fraisse, 1984;Poynter, 1989), perceived size of the stimulus (Ono & Kawahara, 2007;Thomas & Cantor, 1975, 1976, the number denoted by a stimulus (Xuan, Zhan, He, & Chen, 2007), and the amount of energy expended by neurons required to process perceptual stimuli during the period (Eagleman, 2008;Pariyadath & Eagleman, 2007). Strong emotion is also a factor affecting elongation of perceived duration.…”
mentioning
confidence: 99%
“…The estimate for stationary pattern was usually smaller than that for a moving pattern but larger than that for a slowly moving pattern. There have been found other effects of stimulus attributes upon the duration estimation, such as numerosity (Mo, 1971), size (Thomas & Cantor, 1976), complexity (Ornstein, 1969), frequency (Thomas & Brown, 1974), and familiarity (Avant, Lyman, & Antes, 1975). Some ingenious investigators have proposed some models and hypotheses to account for their effects (Fraisse, 1963;Ornstein, 1969;Thomas & Weaver, 1975;Block, 1978Block, , 1979.…”
mentioning
confidence: 99%